Developing pathways to clarify pathogenicity of unclassified variants in Osteogenesis Imperfecta genetic analysis. Issue 12 (30th September 2019) - Balasubramanian, Meena; Hobson, Emma; Skae, Mars; McCaughey, Janine; Stephens, David J.
Abstract: Background: With increased access to genetic testing, variants of uncertain significance (VUS) where pathogenicity is uncertain are being increasingly identified. More than 85% Osteogenesis Imperfecta (OI) patients have pathogenic variants in COL1A1/A2 . However, when a VUS is identified, there are no pathways in place for determining significance. Objective: Define a diagnostic pathway to confirm pathogenicity, providing patients with definitive genetic diagnosis, accurate recurrence risks, and prenatal testing options. Methods: Functional studies on collagen secretion from cultured patient fibroblasts combined with detailed phenotyping and segregation family studies. Results: We demonstrate data from a family with a VUS identified in type I collagen. Family‐1: Six‐year‐old boy with failure‐to‐gain weight, talipes, fractures, on and off treatment with Pamidronate as diagnosis of OI uncertain. Transiliac bone biopsy at 2 years of age demonstrated active new bone formation within periosteum; bone cortices were normal thickness but increased porosity. Trabecular bone showed features of advanced osteoporosis. Genetic testing identified a de novo COL1A1 c.206_208delTGT, p.Leu69del variant. Sibling with similar phenotype but no fractures as yet, tested positive for variant raising concerns regarding her diagnosis, and management. Results from three independent experiments (cell immunofluorescence, collagen secretion assay by Western Blot, and unbiased proteomics) from cultured patient fibroblasts demonstrate COL1A1 c.206_208delTGT, p.Leu69del variant causing a substantial defect to collagen extracellular matrix assembly confirming variant pathogenicity. Conclusion: Access to genetic testing in OI is increasing as advances in genetic technologies decreases cost; a clinical diagnostic pathway needs to be implemented for managing variants identified by such testing. Abstract : Inherited bone fragility disorders, of which Osteogenesis Imperfecta (OI) is the commonest, are rare (1 in 15, 000). In this study, we defined ways to clarify pathogenicity of a variant of uncertain significance leading to bone fragility using advanced sequencing technologies and to characterize the biological consequences of these mutations using advanced molecular cell biology.